EFFECTIVENESS OF STRESS MANAGEMENT TO REDUCE LEVEL STRESS AND EMOTIONAL COPING FOCUSED IN CONVICT AT CLASS IIB PENITENTIARY OF MOJOKERTO CITY - Lilik Marifatul Azizah; Amar Akbar; Imam Zainuri (Bina Sehat Press. Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2018)
Life in custody makes space for inmates restricted and isolated from society. Separated from family, long sentences, and negative public stigma often create prisoner stress. Individual coping responses often occur spontaneously and naturally are emotionally focused coping. But often these efforts are not enough to cause an individual effort to fail to reduce stress. This study aims to prove the effect of stress management on decreasing stress level and emotional focused coping of prisoners in Class II B Correctional Institution Mojokerto. In this research the design used is pre experiment with one group pre and post test design approach. A sample of 30 people was taken with simple random sampling. The group is given counseling about stress management. Data collection of prisoner stress using DASS 42 scale with physical, emotional and behavioral indicator with cronbach za sensitivity value 0.756, while emotional focused coping with self-control indicator, distancing, positive reappraisal, accepting responsibility, and escape with value of reactivity coefficient Î± cronbach 0.837. The influence analysis with the Signed-Rank wilcoxon test showed that stress management was able to decrease the stress level of prisoners with Ñ€ (0,000) <Î± (0.05), and stress management was able to decrease the use of emotionally focused coping prisoners with Ñ€ (0.011) <Î± (0, 05). inmates at Class II B Correctional Institution B Mojokerto. Several factors affecting the stress of prisoners in Class II B Mojokerto Penitentiary include: the perception of prisoners to the Penitentiary neighborhood, the length of crime that must be lived, the lack of entertainment and activities that can be done in the Penitentiary, the lack of opportunities to meet with the family.